Analisis Indeks Diversitas Vegetasi Hutan Sosial Sukobubuk Kabupaten Pati (Studi Terhadap Habitat Vegetasi Pohon Kayu Jati, Balsa, dan Sengon Hutan Sukobubuk) - Ismail, Amrizarois; Linggar Yekti Nugraheni , Bernadia; Purnamasari, Shresta (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
Pati Regency, located in Central Java, is known to have many social forests. One example is the Sukobubuk Social Forest. With the management efforts carried out by the Sukobubuk Rejo Forest Farmers Group (KTH), the condition of the Sukobubuk Social Forest has experienced significant improvements. To assess the extent of this progress, an analysis of the vegetation diversitas index in the forest is needed. This research uses a quantitative approach with a diversitas index calculation method which includes frequency, density, dominance, relative number, significant figure index (INP), and diversitas index (ID). The results show that the level of biodiversitas or diversitas index in the dominant woody vegetation habitat in the Sukobubuk forest is still relatively low. This can be seen from the diversitas index figures for the entire vegetation calculated which are still below number 1 (H'<1), with the highest to lowest order being sengon 0.154115951, teak 0.11926885, and balsa 0.078055196. However, forest management by KTH Sukobubuyk Rejo can be said to have experienced quite a development with conservation efforts, this is marked by the start of growth of vegetation habitat, although not yet significant.